CLINICAL VALUE OF THE SURROGATE INDICATORS OF ATHEROSCLEROSIS IN PATIENTS WITH KNEE OSTEOARTHROSIS CONCURRENT WITH CORONARY HEART DISEASE - S M Noskov; A A Zavodchikov; A V Evgenyeva; A A Lavrukhina; A N Chamorovsky; O N Prokopenko; V S Poletayeva (Научно-практическая ревматология)
Objective: to study the prevalence of a number of surrogate measures of atherosclerosis among patients with knee osteoarthrosis (KOA) and chronic coronary heart disease (CCHD) and to determine the nature of their relationship to their functional state and the amount of muscle mass. Subjects and methods. Twenty patients with KOA and CCHD were examined. The rigidity of the vascular wall was judged from pulse wave velocity (PWV) in the elastic vessels, by calculating a carotid-femoral index (CFI). Endothelial function was evaluated from endothelium-dependent vasodilation (EDVD) in a reactive hyperemia test. Common carotid artery scanning was used to estimate the thickness of the intima-media complex (IMC) in the carotid arteries. A bicycle ergometry exercise was performed in all the patients; exercise tolerance (ET) was determined by the amount of oxygen consumed while calculating a metabolic equivalent (MET). A bioimpedance analyzer was applied to measure the amount of muscle mass, by determining the percentages of active cell mass (ACM%) and lean mass (LM%) of total body weight. The levels of total cholesterol, high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, and triglycerides were determined. A control group consisted of 20 matched individuals without CCHD. Results and discussion. There was a prognostically favorable CFI increase (> 12 m/sec) in 20% of the patients with CCHD and in 10% of the controls (z = 0.15; p = 0.78), endothelial vasomotor dysfunction (EDVD < 10%) in 55% of the patients with CCHD and in 50% of the controls (z = 0.76; p = 0.55); a more than 0.9-mm IMC increase in 60% of the patients with CCHD. The bulk of the patients with pathological vascular rigidity and endothelial vasomotor dysfunction had a low ET. The CCHD patients with a low ET showed significant correlations of CFI and ACM% and LM% (r = -0.36; p < 0.05 and r = -0.39; p < 0.05, respectively), EDVD with ACM% and LM% (r = 0.51; p < 0.05 and r = 0.45; p